Nursing care for a 71-year-old patient suffering from the acute phase of ischemic stroke - Bąk, Ewelina; Kostka, Julia (Quality in Sport, 2024)
Stroke is a significant problem, both clinical and social, leading to disability of the patient. Its occurrence is mainly influenced by modifiable and non-modifiable factors. The golden mean in diagnosis, and then in functioning in everyday life, is the time from the onset of the first symptoms of a stroke and the related method of treatment. Proper care for the patient in the acute phase of stroke is essential for continued functioning at home.